Pemanfaatan E-Marketplace Online Dalam Mengembangkan Potensi Usaha Berbasis Keunggulan Lokal Desa Margalaksana - Dian Rahadian; Yuniar Purwanti; Iman Nasrulloh; Siti Husnul Bariah; Kuntum An Nisa Imania; Dudi Suprihadi (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2019)
The development of information and communication technology is currently experiencing very rapid development. The presence of internet technology has a major impact on various areas of human life. The rapid growth of Small and Medium Enterprises in the Margalaksana Village area of Salawu District is an opportunity for business actors to expand their business reach to market their products by utilizing internet technology. E-Marketplace is an electronic / online product marketing platform that brings together many sellers and buyers to transact with each other. The purpose of this training is to provide understanding and skills to small and medium entrepreneurs, especially in the Margalaksana Village area so that they can develop their business in an online marketplace by utilizing the internet network. This activity is a training part of the community service program carried out by the PKM team and lecturers of the Information Technology Education Study Program.